Nursing interventions in the perioperative period of pressurized intraperitoneal aerosol chemotherapy: A clinical case - Jamilya Zainulina; Nurgul Adiyet; Gulmira Galimova; Aiken Maratkyzy (Astana Medical Journal, 2026)
Introduction. Oncology care in the Republic of Kazakhstan is undergoing dynamic development. One innovative approach is the clinical implementation of the pressurized intraperitoneal aerosol chemotherapy method as part of a scientific and technical project being implemented at the National Scientific Oncology Center to prevent the development and treatment of peritoneal carcinomatosis in advanced gastric cancer. This project not only technically implements the method but also conducts the first study of nursing interventions during the perioperative period of pressurized intraperitoneal aerosol chemotherapy sessions. This aspect is particularly relevant in the context of the scientific literature, as standardized nursing algorithms for pressurized intraperitoneal aerosol chemotherapy are currently being developed in the Republic of Kazakhstan. This clinical case illustrates the specifics of organizing and implementing nursing care for a patient during the perioperative period treated with the pressurized intraperitoneal aerosol chemotherapy method. The patient was admitted to hospital on a planned basis with complaints of difficulty in swallowing solid food and a 6-kilogram weight loss over 6 months. A multidisciplinary team diagnosed cardioesophageal cancer and recommended diagnostic laparoscopy with abdominal swabs for staging and a pressurized intraperitoneal aerosol chemotherapy session. Nursing care at each stage involves a combination of professional and structured actions by the nurse aimed at ensuring patient safety, achieving optimal surgical outcomes, and effective recovery. Keywords: aerosol, peritoneal neoplasms, nursing care, surgical procedures, operative.